Multiproduct Retailing - Rhodes, A. (Review of Economic Studies, 2015)
We study the pricing behaviour of a multiproduct firm, when consumers must pay a search cost to learn its prices. Equilibrium prices are high, because consumers understand that visiting a store exposes them to a hold-up problem. However, a firm with more products charges lower prices, because it attracts consumers who are more price sensitive. Similarly, when a firm advertises a low price on one product, consumers rationally expect it to charge somewhat lower prices on its other products as well. We therefore find that having a large product range, and advertising a low price on one product, are substitute ways of building a “low-price image”. Finally, we show that in a competitive setting each product has a high regular price, with firms occasionally giving random discounts that are positively correlated across products.